FENOMENA BERITA KEKERASAN di MEDIA TELEVISI (Perspektif Teori Kultivasi) NEWS MEDIA PHENOMENON OF VIOLENCE IN TELEVISION (Cultivation Theory Perspective) - Sigit Surahman (Universitas Serang Raya, 2016)
This study focuses on the influence of the intensity of the frequency of the audience watching the news that contain violence. The number of television stations that broadcast news of the violence repeatedly affect children's behavior in everyday life. Booming charge news this violence resulted in all the mainstream media are vying for presenting the news of violence and neglect the effects of what is broadcast. News show as a phenomenon and a momentum to reach the audience as much as possible for television stations. Construction purposes in many television news reality changing audience behavior, since television emerged as a second mother who where viewers can learn a lot through television broadcasts. Cultivation perspective analysis is an analysis that starts from the messaging system to identify patterns of permanent, continuous, overaching of content in television. The division of light viewer, media viewer, and the viewer heavy intensity measured from the time of respondents watching television, the most important thing there is a frequency difference between the intensity of the respondents watch. By using a cultivation perspective on this assessment reveal the intensity of the frequency of watching news of violence can effect/specific impact for the audience.